Vulcanized MXene catalyst as well as preparation method and application thereof

By vulcanizing the MXene material, the stability and cost of electrochemical synthesis of hydrogen peroxide catalysts are solved, and efficient and stable hydrogen peroxide production is achieved.

CN119843314AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411957331.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-18
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art When electrochemical synthesis of hydrogen peroxide, the high cost, scarcity and catalytic stability of the catalyst are insufficient, limiting its large-scale application.

Method used

By vulcanizing the layered MXene material, the reaction active sites are increased, the electrocatalytic activity of the oxygen reduction reaction on hydrogen peroxide is improved, and the stability of the catalyst is improved.

Benefits of technology

The electrocatalytic synthesis of hydrogen peroxide is achieved with high selectivity and long-term stability, reducing production costs and having wide application potential.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a vulcanized MXene catalyst as well as a preparation method and application thereof, and relates to the technical field of catalyst preparation. The MXene material with a layered structure is vulcanized, so that active sites required by the reaction are greatly increased, the electrocatalytic activity of the oxygen reduction reaction on hydrogen peroxide is improved, and the catalyst has good catalytic stability and mechanical stability and can be used for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a sulfided MXene catalyst, a preparation method thereof, and application thereof in hydrogen peroxide production. Background Art

[0002] Hydrogen peroxide (H2O2) is a green and important oxidant that has been widely used in the chemical industry, environmental remediation, and textile manufacturing. Currently, the industrial production of H2O2 mainly relies on energy-intensive anthraquinone technology, which is a multi-step process that not only requires complex and large-scale facilities but also produces a large amount of waste chemicals. In addition, high concentrations of H2O2 may cause high costs and safety issues during storage and transportation. For these reasons, the development of an energy-saving route to reduce the cost of H2O2 synthesis, storage, and transportation has become an emerging trend. Recently, the electrochemical generation of H2O2 from the oxygen reduction reaction (ORR) via 2e transfer has attracted the attention of researchers. However, the development of highly selective and high-performance 2e ORR electrocatalysts is a prerequisite for the production of H2O2.

[0003] Currently, the highest performance catalysts for electrochemical synthesis of hydrogen peroxide use electrocatalysts made of precious metals such as gold, platinum and palladium, which have high ORR activity and H2O2 selectivity. However, their high cost and scarcity hinder their large-scale application. In order to be widely used, it is crucial to study efficient and precious metal-free electrocatalysts. Two-dimensional (2D) carbon-based materials have shown good performance in the electrochemical synthesis of H2O2 due to their abundant reserves, tunable electronic structures and composition diversity. However, as the most promising 2D material, graphene is hindered in its development in practical applications due to its simple chemical properties, only carbon network, scarce surface group types and low conductivity. Therefore, researchers have been developing other potential electrocatalysts.

[0004] MXenes are an emerging type of two-dimensional layered metal carbon / nitrogen compound with the general formula M n+1 X n T x , originating from the precursor MAX phase (M n+1 AX n), where the integer n is 1, 2 or 3, M is an early transition metal, X is carbon, nitrogen or both, A represents a group IIIA or group IVA element, T represents a surface terminal group such as fluorine, oxygen, chlorine or hydroxyl, and x represents the number of the surface functional group. MXenes have excellent intrinsic properties such as high surface area, high metallic conductivity, easy functionalization, environmental protection, antibacterial property, chemical stability, activated metal hydroxide sites and hydrophilicity, making them the preferred candidate materials for applications in environmental remediation, energy storage, catalysis, sensors and electronics. Unlike other two-dimensional materials, the functional group termination groups in MXenes do not rely on any controlled reaction but are generated by the exfoliation process itself. MXenes can overcome the shortcomings of graphene, combining the conductivity of transition metal carbides and the hydrophilicity of hydrogen or oxygen ends with the excellent chemical and structural stability of ceramics. Therefore, since its discovery, people have conducted extensive and in-depth research on the synthesis, properties and applications of MXenes. It has been found that after MXenes are subjected to different modification treatments, their chemical and physical properties can be easily adjusted, and the catalytic activity of modified MXenes catalysts is similar to that of catalysts containing precious metals, or even better, and can be used as a potential catalyst.

[0005] Patent CN113322485B discloses a modified MXene-loaded Ni catalyst, its preparation method, and its application in hydrogen peroxide production. It prepares a catalyst using MXene material as a precursor, and loading metal Ni through post-modification treatment. Among them, MXene (Ti3C2) is used as a carrier, Ni is an active component, and the prepared catalyst is subjected to an experiment of electrochemical synthesis of hydrogen peroxide. Although the invention has high selectivity and low transfer electrons in the process of electrochemical synthesis of hydrogen peroxide, its catalytic stability is only about 3h, which restricts its potential for industrial application. Summary of the invention

[0006] The present invention greatly increases the active sites required for the reaction by sulfurizing the layered MXene material, thereby improving the electrocatalytic activity of the oxygen reduction reaction to hydrogen peroxide. The catalyst has good catalytic stability and mechanical stability and can be used for a long time.

[0007] One of the purposes of the present invention is to provide a method for preparing a novel sulfurized MXene catalyst.

[0008] A second object of the present invention is to provide a sulfurized MXene catalyst prepared by the preparation method.

[0009] The third object of the present invention is to provide an application of the sulfurized MXene catalyst.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] In a first aspect, the present invention provides a method for preparing a sulfurized MXene catalyst, comprising the following steps:

[0012] S1. providing a layered MXene material;

[0013] S2. Dissolve the layered MXene material in a solvent, add carbon disulfide for ultrasonic stirring, and dry; sinter the dried powder at a high temperature to obtain a sulfurized MXene catalyst.

[0014] Step S1:

[0015] There is no particular restriction on the source of the layered MXene material, which can be commercially available or prepared by oneself.

[0016] In some embodiments, the method for preparing the layered MXene material of step S1 comprises the following steps:

[0017] (1) adding the precursor MAX to hydrofluoric acid, heating and etching, cooling, washing, and drying to obtain MXene powder;

[0018] (2) The MXene powder obtained in step (1) is dispersed in water, and an aqueous solution of tetrabutylammonium hydroxide is added for ultrasonic treatment. After separation, the supernatant is collected and freeze-dried to obtain a layered MXene material.

[0019] Preferably, in step (1), the mass concentration of hydrofluoric acid is 35% to 50%;

[0020] Preferably, in step (1), the mass volume ratio of the precursor MAX to the hydrofluoric acid is 1 g:15 mL to 1 g:25 mL;

[0021] Preferably, in step (1), the temperature of the heating etching treatment is 55 to 65° C., and the time is 48 to 96 hours.

[0022] Preferably, in step (2), the mass concentration of the tetrabutylammonium hydroxide aqueous solution is 35% to 50%;

[0023] Preferably, in step (2), the mass volume ratio of MXene powder to tetrabutylammonium hydroxide aqueous solution is 1g:1mL-1g:2mL.

[0024] Preferably, in step (2), the ultrasonic treatment temperature is room temperature, and the ultrasonic treatment time is 20 to 40 minutes.

[0025] MXene materials include but are not limited to Mo2TiC2, Ti4C3, Ti3C2, Ti2C, Mo2C, V3C2, V2C, Hf3C2, Nb3C2, Nb2C, Cr3C2, Ta2C, Ti4N3, and V2N. The typical one is Mo2TiC2-MXene material, and the corresponding precursor MAX is Mo2TiAlC2.

[0026] Step S2:

[0027] In some embodiments, the solvent in step S2 is anhydrous ethanol.

[0028] In some embodiments, in step S2, the mass volume ratio of the layered MXene material to carbon disulfide is 1 g:10 mL-1 g:30 mL, preferably 1 g:25 mL.

[0029] In some embodiments, the ultrasonic stirring temperature in step S2 is room temperature, and the ultrasonic stirring time is 0.5 to 1.5 hours.

[0030] In some embodiments, the drying in step S2 is performed by using a rotary evaporator at 40-55°C.

[0031] In some embodiments, the sintering temperature in step S2 is 500-700° C., and the sintering time is 2-3 hours.

[0032] In a specific embodiment, the method for preparing a sulfurized MXene catalyst comprises the following steps:

[0033] The first step is to add Mo2TiAlC2 (g) powder and 40wt% HF (mL) into a plastic bottle in a ratio of 1:15 to 1:25, and stir the reaction at 55 to 65°C in an oil bath for 48 to 96 hours; cool to room temperature, wash and centrifuge until the pH is neutral, and dry to obtain Mo2TiC2-MXene powder;

[0034] Then, 500-700 mg of the synthesized dry powder was dispersed in 50-70 mL of deionized water, and then 0.5-1.5 mL of 40 wt% tetrabutylammonium hydroxide (TBAOH) was added; ultrasonic treatment was performed for 20-40 min under continuous flow of argon gas, and finally centrifuged at 2000 rpm for 0.5 h, the supernatant in the test tube was collected, and freeze-solidified and dried to obtain layered Mo2TiC2-MXene powder;

[0035] The second step is to dissolve about 500 mg of the layered Mo2TiC2MXene powder obtained in the first step in 50 ml of anhydrous ethanol, add 5-15 ml of carbon disulfide (AR), and stir ultrasonically for 0.5-1.5 h; then use a rotary evaporator to dry at 40-55 ° C; finally, place the obtained powder on a ceramic boat in the center of the furnace and heat it to 500-700 ° C in argon at a heating rate of 2-5 ° C min -1 , keep for 2h, and obtain a black fluffy powder catalyst after cooling.

[0036] In a second aspect, the present invention provides a sulfurized MXene catalyst prepared by the above-mentioned preparation method, comprising a layered MXene material and sulfur loaded on the layered MXene material, wherein the content of sulfur element in the sulfurized MXene catalyst is 5 to 25 wt%, preferably 10 to 20 wt%.

[0037] The main structure of the catalyst is based on layered Mo2TiC2-MXene as a carrier. After sulfurization, the layer structure is not destroyed. S will react with the structural layer Mo to form Mo-S. The active components are mainly Mo-S sites at the edge of the structural layer. After etching, a layered MXene material with high conductivity is obtained, which promotes the transfer of electrons. The desired catalyst is obtained by sulfurization. The sulfurization treatment greatly increases the active sites required for the reaction and improves the electrocatalytic activity of the oxygen reduction reaction to hydrogen peroxide, so that the catalyst material can directly electrocatalyze the synthesis of H2O2 in situ at room temperature.

[0038] The preparation method of the catalyst is simple and the catalyst material is stable. Through electrochemical testing, it is found that the catalyst can efficiently and selectively reduce oxygen to produce hydrogen peroxide, and the catalyst has good catalytic stability and mechanical stability, can be used for a long time, and has great application potential.

[0039] In a third aspect, the present invention provides an application of the above-mentioned sulfurized MXene catalyst in the production of hydrogen peroxide.

[0040] In some embodiments, the applying comprises the following steps:

[0041] The sulfide MXene catalyst, Nafion solution, ultrapure water and anhydrous ethanol are prepared into a solution, the solution is dropped on a glassy carbon disk, and dried at room temperature, as a working electrode, a carbon rod as a counter electrode, and a Hg / HgO electrode as a reference electrode to produce hydrogen peroxide.

[0042] Preferably, the added mass of the sulfide MXene catalyst is 5 to 10 mg, and the mass volume ratio of the sulfide MXene catalyst to the Nafion solution is 1:2 mg / μL to 1:4 mg / μL; the volume ratio of anhydrous ethanol to ultrapure water is 1:1-1:1.5, and the total volume is 1 mL.

[0043] The direct in-situ production method can not only continuously synthesize H2O2, but also allows small-scale and decentralized production. The ORR electrochemical pathway has the characteristics of low energy consumption, low cost and high efficiency.

[0044] Technical effects:

[0045] The catalyst of the present invention mainly uses MXene material (Mo2TiC2) as a carrier, and is successfully sulfurized to produce more active sites, wherein the loading amount of sulfur element is 10 to 20 wt%, and the prepared catalyst is used to electrochemically synthesize hydrogen peroxide through a two-electron oxygen reduction reaction.

[0046] The catalyst of the present invention has good performance in electrocatalytic production of hydrogen peroxide, high charge transfer ability and long-term stable working ability: H2O2 selectivity is more than 90%, the charge transfer number is closer to 2e, and it can continue to work for 40 hours at a voltage of 0.7V vs.RHE.

[0047] The main reasons for its excellent performance are:

[0048] 1. The catalyst obtained by sulfidation treatment of Mo2TiC2 material still maintains the lamellar structure, and the generation of Mo-S structural layer will produce more edge sites. In addition, the presence of Ti layer can also induce a large number of defects in the Mo-S structural layer, which helps to generate more Mo active sites, improve its intrinsic activity, and increase the conductivity of the basal surface.

[0049] 2. The three-dimensional structure of the MXene support can highly transfer the accessibility of ions from the electrolyte to the active sites of the catalyst. The strong conjugation between the Mo-S structure layer and the Ti layer and the C layer provides a resistance-free path that promotes charge transfer, with lower charge transfer resistance, which has better electrochemical performance and fast kinetics.

[0050] 3. The specific surface area of ​​the catalyst is increased. The surface area that is most easily electrolyzed comes from the three-dimensional structure of the MXene carrier and the Mo-S structure layer. The S-Mo2TiC2 material has a multi-layer interconnected three-dimensional structure. This multi-layer interconnected structure greatly promotes the accessibility of the catalyst's rich active sites, as well as the electrolyte's infiltration and charge transfer, thereby achieving efficient electrocatalytic production of hydrogen peroxide.

[0051] In summary, a novel sulfided MXene material catalyst prepared in the present invention exhibits higher H2O2 selectivity, a charge transfer number closer to 2e, and good working stability. This makes the catalyst a promising candidate catalyst and great potential for large-scale practical application to further enhance the potential of electrocatalytic H2O2 production at the industrial level.

[0052] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. DETAILED DESCRIPTION

[0053] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0054] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0055] Mo2TiAlC2 was from Jilin Yiyi Technology Co., Ltd.;

[0056] Tetrabutylammonium hydroxide was from Aladdin Reagent (Shanghai) Co., Ltd.;

[0057] Carbon disulfide was from Aladdin Reagent (Shanghai) Co., Ltd.

[0058] Example 1

[0059] The preparation of catalyst S1 comprises the following steps:

[0060] Step 1: Mo2TiAlC2 (1.5 g) powder was slowly added to 40 wt% HF (30 mL), and the solution was stirred in an oil bath at 60°C for 72 h. After 72 h, the solution was cooled in a room temperature environment, and then continuously washed with deionized water and centrifuged. When the pH of the poured supernatant was neutral, the bottom solid was placed in a refrigerator for freezing and solidification, and then dried with a freeze dryer to obtain catalyst M1.

[0061] Step 2: Disperse about 600 mg of catalyst M1 into 60 mL of deionized water, and then add 1 mL of 40 wt% tetrabutylammonium hydroxide (TBAOH) aqueous solution. Ultrasonic treatment was performed for 0.5 h under continuous argon flow, and centrifuged at 2000 rpm for 0.5 h. After that, the supernatant in the test tube was collected to obtain a layered Mo2TiC2-MXene solution. The solution was placed in a refrigerator for freezing and solidification, and then dried with a freeze dryer to obtain catalyst M2.

[0062] Step 3: Preparation of sulfided Mo2TiC2-based MXene material: About 500 mg of M2 powder was dissolved in 50 ml of anhydrous ethanol, and then 10 ml of carbon disulfide was added, and ultrasonic stirring was performed for 1 hour to form a uniform solution. Then it was dried at 45 ° C using a rotary evaporator. The obtained powder was placed on a ceramic boat in the center of the furnace and heated to 650 ° C in argon at a heating rate of 2 ° C / min for 2 hours. After cooling, the catalyst S1 was finally obtained; the sulfur content was about 16.1 wt%.

[0063] Example 2

[0064] The preparation of catalyst S2 comprises the following steps:

[0065] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0066] Step 3: Preparation of sulfided Mo2TiC2-based MXene material: About 500 mg of catalyst M2 powder was dissolved in 50 ml of anhydrous ethanol, and then 10 ml of carbon disulfide was added, and ultrasonic stirring was performed for 1 hour to form a uniform solution. Then it was dried at 45 ° C using a rotary evaporator. The obtained powder was placed on a ceramic boat in the center of the furnace and heated to 650 ° C in argon at a heating rate of 2 ° C / min for 4 hours. After cooling, the catalyst S2 was finally obtained; the sulfur content was 20.3 wt%.

[0067] Example 3

[0068] The preparation of catalyst S3 comprises the following steps:

[0069] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0070] Step 3: Preparation of sulfurized Mo2TiC2-based MXene material: About 500 mg of catalyst M2 powder was dissolved in 50 ml of anhydrous ethanol, and then 10 ml of carbon disulfide was added, and ultrasonic stirring was performed for 1 hour to form a uniform solution. Then it was dried at 45 ° C using a rotary evaporator. The obtained powder was placed on a ceramic boat in the center of the furnace and heated to 650 ° C in argon at a heating rate of 2 ° C / min for 1 hour. After cooling, the catalyst S3 was finally obtained; the sulfur content was 10.7 wt%.

[0071] Example 4

[0072] The preparation of catalyst S4 comprises the following steps:

[0073] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0074] Step 3: Preparation of sulfided Mo2TiC2-based MXene material: About 500 mg of catalyst M2 powder was dissolved in 50 ml of anhydrous ethanol, and then 10 ml of carbon disulfide was added, and ultrasonic stirring was performed for 1 hour to form a uniform solution. Then it was dried at 45 ° C using a rotary evaporator. The obtained powder was placed on a ceramic boat in the center of the furnace and heated to 650 ° C in argon at a heating rate of 5 ° C / min for 2 hours. After cooling, the catalyst S4 was finally obtained; the sulfur content was 13.4 wt%.

[0075] Example 5

[0076] The preparation of catalyst S5 comprises the following steps:

[0077] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0078] Step 3: Prepare the sulfurized Mo2TiC2-based MXene material. Dissolve about 500 mg of catalyst M2 powder in 50 ml of anhydrous ethanol, add 10 ml of carbon disulfide, and stir ultrasonically for 1 hour to form a uniform solution. Then dry it at 55°C using a rotary evaporator. Place the obtained solid on a ceramic boat in the center of the furnace and heat it to 650°C in argon at a heating rate of 2°C / min for 2 hours. After cooling, the catalyst S5 is finally obtained; the sulfur content is 5.4wt%.

[0079] Example 6

[0080] The preparation of catalyst S6 comprises the following steps:

[0081] Step 1 and step 2 are the same as step 1 and step 2 of embodiment 1.

[0082] Step 3: Prepare the sulfurized Mo2TiC2-based MXene material. Dissolve about 500 mg of catalyst M2 powder in 50 ml of anhydrous ethanol, add 10 ml of carbon disulfide, and stir ultrasonically for 1 hour to form a uniform solution. Then dry it at 45°C using a rotary evaporator. Place the obtained solid on a ceramic boat in the center of the furnace and heat it to 500°C in argon at a heating rate of 2°C / min for 2 hours. After cooling, the catalyst S6 is finally obtained; the sulfur content is 8.3wt%.

[0083] Comparative Example 1

[0084] Preparation of sulfided Mo2TiC2-based MXene materials: About 500 mg of catalyst M1 powder was dissolved in 50 ml of anhydrous ethanol, and then 10 ml of carbon disulfide was added. Ultrasonic stirring was performed for 1 hour to form a uniform solution. Then it was dried at 45 ° C using a rotary evaporator. The obtained powder was placed on a ceramic boat in the center of the furnace and heated to 650 ° C in argon at a heating rate of 2 ° C / min for 2 hours. After cooling, the catalyst S7 was finally obtained.

[0085] Comparative Example 2

[0086] Preparation of oxidized Mo2TiC2-based MXene material: About 500 mg of catalyst M2 powder was placed in a ceramic boat and heated and oxidized in a muffle furnace. It was heated to 650°C in air at a heating rate of 2°C / min and maintained for 2 hours. After cooling, catalyst O1 was finally obtained.

[0087] Test example

[0088] Preparation of working electrode:

[0089] Add 5 mg of the catalyst to be tested, 10 μL of Nafion solution (5 wt%), 600 μL of ultrapure water, and 400 μL of anhydrous ethanol (in a ratio of 1:2:120:80) to a centrifuge tube. After thorough mixing, ultrasonic treatment was performed for 0.5 h to form a uniform ink, and the ink was dropped onto a glassy carbon disk and dried at room temperature.

[0090] The carbon rod was used as the counter electrode and the Hg / HgO electrode was used as the reference electrode.

[0091] Performance test of electrocatalytic hydrogen peroxide production:

[0092] The experiments of electrochemical synthesis of hydrogen peroxide in this paper were all completed by CHI760E electrochemical workstation and rotating disk electrode device. The test was carried out under normal temperature and pressure environment, and the electrolyte was 0.1M KOH solution (alkaline, pH=13).

[0093] (I D : disk current; I R : Ring current).

[0094] Electrochemical performance (disk current and ring current) test:

[0095] In order to eliminate the air in the electrolyte as much as possible, the electrolyte needs to be ventilated with N2 for 30 minutes. Then, the cyclic voltammetry (CV) curve is tested at a scan rate of 50mV / s for at least 40 cycles until the CV curve remains stable. The electrolyte is then ventilated with oxygen for 30 minutes. After that, the cycle is repeated 20 times at a scan rate of 10mV / s until the CV curve remains stable. Finally, the linear sweep voltammogram (LSV) in the oxygen-saturated electrolyte is measured by polarization curve and rotating ring disk electrode (RRDE). The ORR polarization curve is saved by adjusting the rotating disk electrode device so that the electrode speed is kept at 1600rpm and the scan rate is kept at 10mV / s for measurement.

[0096] Stability test:

[0097] The electrochemical workstation was used to control the voltage of the working electrode and measure the change of the current of the working electrode over time. The specific experimental method was to explore the continuous working time of the catalyst under the condition of applying a voltage of 0.7V vs. RHE. The results showed that the catalyst S1 with the best performance in electrocatalytic hydrogen peroxide production could work stably for more than 40 hours without obvious overpotential changes, indicating that the catalyst has good stability and can be used for a long time.

[0098] The catalysts prepared in the above examples and comparative examples were tested for selectivity of electrochemical production of hydrogen peroxide. The test results are shown in Table 1.

[0099] Table 1 Selectivity test of catalyst electrochemical production of hydrogen peroxide

[0100] catalyst Hydrogen peroxide selectivity / % M1 36 M2 53 S1 90 S2 76 S3 81 S4 85 S5 71 S6 75 S7 48 O1 40

[0101] From Table 1, we can see that the catalyst S1 prepared by the present invention has a significantly improved hydrogen peroxide selectivity compared to the original Mo2TiC2-MXene catalyst. In addition, the catalysts prepared by changing different reaction conditions, although the hydrogen peroxide selectivity is also improved compared to the Mo2TiC2-MXene catalyst, the modification effect is reduced. This shows that the change in reaction conditions affects the degree of sulfurization of the Mo2TiC2-MXene catalyst, fails to produce more active sites, and thus affects the charge transfer and electrochemical hydrogen peroxide production capabilities.

[0102] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A method for preparing a sulfurized MXene catalyst, characterized in that: The following steps are involved: S1. providing a layered MXene material; S2. Dissolve the layered MXene material in a solvent, add carbon disulfide for ultrasonic stirring, and dry; sinter the dried powder at a high temperature to obtain a sulfurized MXene catalyst.

2. The preparation method according to claim 1, characterized in that: The method for preparing the layered MXene material of step S1 comprises the following steps: (1) adding the precursor MAX to hydrofluoric acid, heating and etching, cooling, washing, and drying to obtain MXene powder; (2) The MXene powder obtained in step (1) is dispersed in water, and an aqueous solution of tetrabutylammonium hydroxide is added for ultrasonic treatment. After separation, the supernatant is collected and freeze-dried to obtain a layered MXene material.

3. The preparation method according to claim 2, characterized in that: In step (1), the mass concentration of hydrofluoric acid is 35% to 50%; In step (1), the mass volume ratio of the precursor MAX to the hydrofluoric acid is 1 g:15 mL to 1 g:25 mL; In step (1), the temperature of the heating etching treatment is 55 to 65° C. and the time is 48 to 96 hours.

4. The preparation method according to claim 2, characterized in that: In step (2), the mass concentration of the tetrabutylammonium hydroxide aqueous solution is 35% to 50%; In step (2), the mass volume ratio of MXene powder to tetrabutylammonium hydroxide aqueous solution is 1 g: 1 mL-1 g: 2 mL; In step (2), the ultrasonic treatment time is 20 to 40 minutes.

5. The preparation method according to claim 1, characterized in that: The MXene material is one of Mo2TiC2, Ti4C3, Ti3C2, Ti2C, Mo2C, V3C2, V2C, Hf3C2, Nb3C2, Nb2C, Cr3C2, Ta2C, Ti4N3, and V2N, preferably Mo2TiC2.

6. The preparation method according to claim 1, characterized in that: The solvent in step S2 is anhydrous ethanol.

7. The preparation method according to claim 1, characterized in that: In step S2, the mass volume ratio of the layered MXene material to carbon disulfide is 1 g:10 mL-1 g:30 mL; The drying in step S2 is performed by using a rotary evaporator at 40 to 55° C.; The sintering temperature of step S2 is 500-700° C., and the sintering time is 2-3 hours.

8. A sulfided MXene catalyst, characterized in that The sulfurized MXene catalyst is prepared by the preparation method according to any one of claims 1 to 7; The sulfurized MXene catalyst comprises a layered MXene material and sulfur supported on the layered MXene material, wherein the content of sulfur in the sulfurized MXene catalyst is 5 to 25 wt %, preferably 10 to 20 wt %.

9. Use of the sulfided MXene catalyst according to claim 8 in the production of hydrogen peroxide.

10. The use according to claim 9, characterized in that: The application comprises the following steps: The sulfide MXene catalyst, Nafion solution, ultrapure water and anhydrous ethanol are prepared into a solution, the solution is dropped on a glassy carbon disk, and dried at room temperature, as a working electrode, a carbon rod as a counter electrode, and a Hg / HgO electrode as a reference electrode to produce hydrogen peroxide.

Citation Information

Patent Citations

  • A modified MXene-supported Ni catalyst, its preparation method, and its application in hydrogen peroxide production.

    CN113322485B

  • MXene and transition metal sulfide composite nano-catalyst based on fiber skeleton and preparation method thereof

    CN112553641A

  • Preparation method and application of iodine atom doped double transition metal MXene catalyst

    CN114657599A

  • Molybdenum disulfide / titanium carbonized MXene heterojunction catalyst as well as preparation method and application thereof

    CN116459852A

  • Preparation method of sulfur-doped MXene material as well as product and application of sulfur-doped MXene material

    CN117049543A